2014
DOI: 10.1080/03081087.2014.947984
|View full text |Cite
|
Sign up to set email alerts
|

Spectral radius and Hamiltonian properties of graphs

Abstract: Let G be a graph with minimum degree δ. The spectral radius of G, denoted by ρ(G), is the largest eigenvalue of the adjacency matrix of G. In this note we mainly prove the following two results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…
This paper presents sufficient conditions for Hamiltonian paths and cycles in graphs. Letting λ (G) denote the spectral radius of the adjacency matrix of a graph G, the main results of the paper are:(1) Let k ≥ 1, n ≥ k 3 /2 + k + 4, and let G be a graph of order n, with minimum degree(2) Let k ≥ 1, n ≥ k 3 /2 + k 2 /2 + k + 5, and let G be a graph of order n, with minimum degreethen G has a Hamiltonian path, unlessIn addition, it is shown that in the above statements, the bounds on n are tight within an additive term not exceeding 2. cycles in G. This work motivated further research, as could be seen, e.g., in [1,10,13,14,15,16,17,21].The aim of this paper is to extend some recent results by Benediktovich [1], Li and Ning [14], and Ning and Ge [17]. To state those results we need to introduce three families of extremal graphs, which are denoted by L k (n) , M k (n) and N k (n).Write K s and K s for the complete and the edgeless graphs of order s. Given graphs G and H, write G ∨ H for their join and G + H for their disjoint union.The graphs L k (n) .
…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…
This paper presents sufficient conditions for Hamiltonian paths and cycles in graphs. Letting λ (G) denote the spectral radius of the adjacency matrix of a graph G, the main results of the paper are:(1) Let k ≥ 1, n ≥ k 3 /2 + k + 4, and let G be a graph of order n, with minimum degree(2) Let k ≥ 1, n ≥ k 3 /2 + k 2 /2 + k + 5, and let G be a graph of order n, with minimum degreethen G has a Hamiltonian path, unlessIn addition, it is shown that in the above statements, the bounds on n are tight within an additive term not exceeding 2. cycles in G. This work motivated further research, as could be seen, e.g., in [1,10,13,14,15,16,17,21].The aim of this paper is to extend some recent results by Benediktovich [1], Li and Ning [14], and Ning and Ge [17]. To state those results we need to introduce three families of extremal graphs, which are denoted by L k (n) , M k (n) and N k (n).Write K s and K s for the complete and the edgeless graphs of order s. Given graphs G and H, write G ∨ H for their join and G + H for their disjoint union.The graphs L k (n) .
…”
mentioning
confidence: 72%
“…In addition, it is shown that in the above statements, the bounds on n are tight within an additive term not exceeding 2. cycles in G. This work motivated further research, as could be seen, e.g., in [1,10,13,14,15,16,17,21].…”
mentioning
confidence: 74%
“…Fiedler and Nikiforov [9] firstly gave sufficient conditions in terms of the spectral radius of a graph or its complement for the existence of Hamilton cycles. This work motivated further research, one may refer to [1,18,19,23,26,27,28,30]. Recently, by imposing the minimum degree of a graph as a new parameter, Li and Ning [14,15] extended some the results in [9,18,23].…”
Section: Introductionmentioning
confidence: 99%
“…This work motivated further research, one may refer to [1,18,19,23,26,27,28,30]. Recently, by imposing the minimum degree of a graph as a new parameter, Li and Ning [14,15] extended some the results in [9,18,23]. Now, their results were improved by Nikiforov [22], Chen et al [5], Ge et al [10] and Li et al [17], in some sense.…”
Section: Introductionmentioning
confidence: 99%
“…For terminology and notations not defined here, we refer the reader to Bondy and Murty [6]. see [7,12,29,22,18,21,23,19,20]. Among these results, the following one has received much attention, which is a corollary of a theorem of Ore [25] and of Bondy [5], independently.…”
Section: Introductionmentioning
confidence: 99%